Cara Mudah Belajar UI/UX : Pelatihan Membuat UI/UX untuk Pemula bagi Siswa SMAK Untung Suropati Krian - Endra Rahmawati (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
SMAK Untung Suropati Krian is one of the institutions that wants to produce the students with computer skills, especially in the field of UI / UX. Students with basic UI / UX skills can be used as a provision for future work. The Training Activity on How to Easily Create UI / UX Designs for Beginners for SMAK Untung Suropati Krian Students has aim of providing basic UI / UX concepts to students, introducing the stages of creating UI / UX designs based on general methodologies, starting from making UI sketches to simple prototypes, increasing insight into the use of the Figma to design simple prototypes. In order to improve quality of students, 13 selected students were sent to take part in UI / UX training by learning about Crazy-8 Practice. All application design sketch ideas can be poured out at this stage within 5-8 minutes to produce 8 sketch forms. The Crazy-8 method is also considered the easiest method to start the UI / UX design process. The results of participant feedback showed that 95% of students gained new insights from this training and ease in learning the material provided, namely making Crazy-8 instantly.